Aplicação foliar de doses de manganês em dois estádios fenológicos da soja RR sob manejo pós-emergente de glyphosate - Nava, Ivair André (2013)
With the increasing advancement of the RR soybean in Brazil, unofficial technical notes proposed that the herbicide glyphosate applied as post-emergence might bring injuries or nutritional imbalance as well suggesting the necessity of supplemental addition of manganese (Mn) through the leaves, to correct its deficiency. The goal of this study was to evaluate the influence of doses and stages of application of commercial fertilizer with Mn, on the foliar content of the major nutrients and the components of production and productivity of RR soybean, treated with glyphosate on post-emergence method to control weeds. Thus, the application of foliar fertilizer with Mn was evaluated in two phenological stages (V4 e V6) and in Five doses (0,00; 56,75; 113,50; 170,50 and 227,00 g ha-1 de Mn) on a eutroferric Oxisol (LVef) with applications on fields and greenhouses. The results indicated that the application of foliar fertilizer doses with Mn on the implementation stages, only favored the accumulation of micronutrient Mn on the leaf tissue of RR soy on the field, the way that the application of glyphosate in the recommended dose of Glyphosate had no effect on foliar concentration of others evaluated nutrients, on the other hand, tests in the greenhouse indicated that the application of foliar fertilizer on the V4 stage decreased the N content and increased the Ca compared to the V6, which had the opposite result, with increasing on the N and decreasing of the leaf Ca. The fertilization with Mn resulted in increasing foliar content of this element when applied on V6 stage in controlled situations, however, dosages greater than 112,24 g ha-1 of Mn are not justified, and are considered the critical point for a recommendation on the soil evaluated. The yield components and grain productivity were not affected by treatments on the Field experiment, the same way, the application of foliar fertilizer with Mn did not provide increments on the production components on the RR soybean conducted in a greenhouse